Impact of Covid-19 on the Malaysian stock market - Goh, Yi Min (2021)
Since its beginning of first case in Wuhan, China, the COVID-19 pandemic has caused a havoc around the world resulting in more than 31 million confirmed cases (22 September 2020). COVID19 pandemic was first declared as pandemic on March 11 by the World Health Organisation. The pandemic has triggered a major impact on global economic activity and in turn affected the global financial market, including Malaysia.